Education in a Functional Structural Perspective and Conflict Regarding Social Relations in Society - Wasilah, Siti (Lembaga Penelitian dan Pendidikan Mandala, 2023)
In the structural functional approach, society is seen as a collection of interrelated parts. In society, reciprocity and symbiotic relationships are mutualism. A system is dynamic when it strives towards equilibrium. The existence of social dysfunction or social differences can eventually be resolved by itself as a result of adaptation and institutionalization processes. This research aims at How Education in a Functional Structural Perspective and Conflicts About Social Relations in Society. In this study the author of this study was written using library techniques. Reading the latest literature provides primary data. the results of this research include that Learning or Education is a process of changing the behavior of both individuals and groups in an effort to mature humans through teaching and training efforts and also called education is a way and process and act of educating, Structural Functional Knowledge recognizes that Functionalism or Structural theory focuses on Social integration, social stability, and consensus on key values